Leveraging social capital of the church for development: A case study of a farming community in Wellington - Beukes, Jacques W. (HTS teologiese studies, 2019)
This article explores how a farming community in Wellington (Bovlei) moved from dependence towards an empowered community through non-profit organisations’ (NPOs) transformative community development initiatives, undertaken together with the church’s social capital. This example serves as the backdrop to explore critical viewpoints by various scholars who are critical about how the church engages in an unequal and unjust society. The critical questions that remain are the following; who is the church?, what is the church’s role as a change agent? and how should churches leverage social capital for development? Although various definitions have been given in conceptualising the church and its role in society, through this article, the author engages with the social capital theory in understanding how the transformation came about in this community by describing the churches’ involvement through a case study.